Interactions between Golli‐MBP and Th1/Th2 cytokines in patients with oral lichen planus. (18th March 2013) - Ding, M; Zeng, J; Sroussi, H; Yu, J; Xu, J; Cheng, X; Fan, Y
<x xml:space="preserve">Abstract</x> Objective Oral lichen planus (OLP) is a prevalent cell‐mediated autoimmune disease of unknown etiology. Disruption in the Th1/Th2 equilibrium has been suspected to contribute to the pathogenesis of OLP. In this study, we aimed at exploring, in OLP, the interactions between Th1/Th2 cytokines and Golli‐MBP, a regulator of autogenic T cells. Subjects and Methods Thirty‐six OLP patients aged 18–79 and nineteen control subjects aged 20–69 were enrolled in the dental clinics of Nanjing Medical University. OLP was diagnosed clinically and verified by histopathological examination. All subjects were free of other autoimmune diseases. Peripheral blood mononuclear cells (PBMC) and serum were collected from all subjects. Gene expression and protein levels of Golli‐MBP, IFN‐γ and IL‐4 were measured, respectively, by semiquantitative reverse transcription polymerase chain reaction and enzyme‐linked immunosorbent assay. Result When compared with control, PBMC and serum from OLP patients exhibited a significantly higher expression and concentration of Golli‐MBP and IL‐4 and lower levels of IFN‐γ. A strong negative correlation (r = −0.838, P < 0.000) was detected between the ratio of IFN‐γ/IL‐4 and Golli‐MBP gene expression in PBMCs of OLP patients. Conclusion These data support a potential link between Golli‐MBP and the dysregulation of the Th1/Th2 equilibrium in OLP.